54.2k views
2 votes
If f(x)= x2-5 and g(x)= -3x + 2, find f(g(x))

If f(x)= x2-5 and g(x)= -3x + 2, find f(g(x))-example-1

1 Answer

5 votes

Answer:

D. 9x² - 12x - 1

Step-by-step explanation:

To find f(g(x)), we need to replace x by g(x) as follows:

f(x) = x² - 5

f(g(x)) = (g(x))² - 5

Then, g(x) is equal to -3x + 2, so replacing g(x) by (-3x + 2), we get:

f(g(x)) = (g(x))² - 5

f(g(x)) = (-3x + 2)² - 5

f(g(x)) = (-3x)² + 2(-3x)(2) + 2² - 5

f(g(x)) = 9x² - 12x + 4 - 5

f(g(x)) = 9x² - 12x - 1

Therefore, the answer is D. 9x² - 12x - 1

User Varun Chandak
by
4.9k points